Nonaqueous electrolyte for lithium secondary battery and lithium secondary battery containing same
The introduction of an imidazolium sulfonate-based compound in the nonaqueous electrolyte of lithium secondary batteries addresses the issue of high-temperature degradation by neutralizing Lewis acids and forming a reinforced coating, resulting in improved high-temperature stability and lifespan.
Patent Information
- Application Number
- JP2024557785
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-30
- Filing Date
- 2023-03-30
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2043-03-30
AI Technical Summary
Lithium secondary batteries face degradation and performance deterioration when operated at high temperatures due to electrolyte decomposition, leading to the generation of Lewis acids and subsequent damage to the electrode coatings.
A nonaqueous electrolyte solution is developed that includes an imidazolium sulfonate-based compound, which acts as a Lewis base to neutralize Lewis acids and form a reinforced coating on the electrodes, thereby enhancing the battery's high-temperature stability and lifespan.
The use of the imidazolium sulfonate-based compound in the nonaqueous electrolyte effectively prevents the deterioration of battery performance at high temperatures, improving the battery's high-temperature storage characteristics and reducing self-discharge and resistance.
Smart Images

Figure 2025511093000001 
Figure 2025511093000002 
Figure 2025511093000003
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0039951, dated March 30, 2022, and all contents disclosed in the documents of that Korean patent application are incorporated herein by reference.
[0002] The present invention relates to a non-aqueous electrolyte for a lithium secondary battery and a lithium secondary battery containing the same. [Background technology]
[0003] Lithium secondary batteries are generally manufactured by forming an electrode assembly by interposing a separator between a positive electrode including a positive electrode active material made of a lithium-containing transition metal oxide and a negative electrode including a negative electrode active material capable of storing lithium ions, inserting the electrode assembly into a battery case, injecting a non-aqueous electrolyte solution that serves as a medium for transferring lithium ions, and then sealing the battery case.
[0004] Lithium secondary batteries can be miniaturized and have high energy density and operating voltage, and therefore are applied in various fields such as mobile devices, electronic products, electric vehicles, etc. As the fields of application of lithium secondary batteries become more diverse, the required physical property conditions are also gradually becoming more stringent. In particular, there is a demand for the development of lithium secondary batteries that can be stably operated even under high temperature conditions and have long life characteristics.
[0005] On the other hand, when a lithium secondary battery is operated under high temperature conditions, the LiPF 6 From lithium salts such as PF 6 - The anion is thermally decomposed to form PF 5 This can generate Lewis acids such as HF, which react with water to generate HF. 5The decomposition products of the electrolyte, such as HF, may not only destroy the coating formed on the surface of the electrode, but may also cause a decomposition reaction of the organic solvent. In addition, the decomposition products of the electrolyte may react with the decomposition products of the positive electrode active material to dissolve transition metal ions, and the dissolved transition metal ions may be electrodeposited on the negative electrode and destroy the coating formed on the surface of the negative electrode.
[0006] If the electrolyte decomposition reaction continues on such a destroyed coating, the battery's performance will further deteriorate, so there is a demand for the development of secondary batteries that can maintain excellent performance even under high temperature conditions. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Korean Patent Publication No. 10-2003-0061219 Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention is intended to solve the above problems, and provides a non-aqueous electrolyte that contains an imidazolium sulfonate-based compound, thereby removing decomposition products of the electrolyte and forming a reinforced coating on the electrode, and a lithium secondary battery that contains the same and exhibits long life characteristics even when operated at high temperatures. [Means for solving the problem]
[0009] According to one embodiment, the present invention provides a non-aqueous electrolyte for a lithium secondary battery, comprising a lithium salt, an organic solvent, and a compound represented by the following Chemical Formula 1:
[0010] [ka]
[0011] In the above Chemical Formula 1, R is O- or OR1, wherein R1 is hydrogen; or an alkyl group having 1 to 10 carbon atoms; L1 is a direct bond; or an alkylene group having 1 to 30 carbon atoms; L2 is an alkylene group having 1 to 10 carbon atoms.
[0012] According to another embodiment, the present invention provides a lithium secondary battery including a positive electrode including a positive electrode active material, a negative electrode including a negative electrode active material, a separator interposed between the positive electrode and the negative electrode, and a non-aqueous electrolyte for the lithium secondary battery. Effect of the Invention
[0013] The nitrogen atom of the cation moiety in the structure of the compound represented by Chemical Formula 1, which is contained as an additive in the nonaqueous electrolyte according to the present invention, acts as a Lewis base, thereby effectively removing Lewis acids generated as decomposition products of the electrolyte, and forming sulfonates (-RSO 3 - ) and the propargyl group (-CH 2 Since the coating on the positive or negative electrode can be strengthened by the addition of C≡CH), when used in a lithium secondary battery, it can realize a lithium secondary battery with improved high-temperature storage characteristics and improved self-discharge due to dissolution of the positive electrode. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The present invention will now be described in more detail. Generally, LiPF is widely used as an electrolyte for lithium secondary batteries. 6 The anions contained in lithium salts such as these are converted to hydrogen fluoride (HF) and PF by thermal decomposition or moisture. 5 Such decomposition products have acidic properties and deteriorate the coating or electrode surface in the battery.
[0015] Due to the decomposition products of the electrolyte and structural changes in the positive electrode caused by repeated charging and discharging, transition metals in the positive electrode are easily dissolved into the electrolyte, and the dissolved transition metals are redeposited on the positive electrode, increasing the resistance of the positive electrode. Furthermore, when the dissolved transition metals move to the negative electrode through the electrolyte, they are electrodeposited on the negative electrode and grow, causing an internal short circuit, which causes self-discharge of the negative electrode and causes low voltage failure. In addition, when the dissolved transition metals are electrodeposited on the negative electrode, they destroy the solid electrolyte interphase (SEI) film, which causes additional electrolyte decomposition reactions, resulting in problems such as consumption of lithium ions and increased resistance.
[0016] In addition, during initial activation of the battery, a protective coating is formed on the positive and negative electrodes due to a reaction of the electrolyte. If the coating becomes unstable for the reasons described above, additional electrolyte decomposition will occur during charging / discharging or exposure to high temperatures, accelerating battery degradation and generating gas.
[0017] Therefore, the present inventors have developed a sulfonate (-RSO 3 - ) and the propargyl group (-CH 2 The compound represented by the following chemical formula 1 containing sulfonate (-RSO 3 - ) is reduced at the negative electrode to form a polymerization structure and LiSO 3 Forms a coating film based on the propargyl group (-CH 2 In the case of C≡CH), it is reduced to generate propargyl radicals, which are then polymerized to form a thin, dense coating on the surface of the negative electrode. In addition, the compound represented by the following formula 1 can be used to reduce the HF and PF 5 It has been confirmed that the non-aqueous electrolyte containing such a Lewis base functional group is effective in preventing battery degradation even at high temperatures of 40°C or higher. Each of the configurations of the present invention will be described in more detail below.
[0018] [Non-aqueous electrolyte] The present invention provides a non-aqueous electrolyte for a lithium secondary battery, comprising a lithium salt, an organic solvent, and a compound represented by the following Chemical Formula 1: Each component will be specifically described below.
[0019] (1) Compound represented by chemical formula 1 The non-aqueous electrolyte of the present invention contains a compound represented by the following chemical formula 1.
[0020] [ka]
[0021] In the above Chemical Formula 1, R is O - or OR1, wherein R1 is hydrogen; or an alkyl group having 1 to 10 carbon atoms; L1 is a direct bond; or an alkylene group having 1 to 30 carbon atoms; L2 is an alkylene group having 1 to 10 carbon atoms.
[0022] The compound represented by Chemical Formula 1 has the effect of strengthening the coating on the electrode due to its structure containing sulfonate and propargyl. The sulfonate (-RSO 3 - ) is reduced at the negative electrode to form a polymerization structure and LiSO 3 In addition, by including the sulfonate in the structure, the LUMO value of the compound of Chemical Formula 1 can be lowered, and the reducing property of the negative electrode can be further improved.
[0023] In addition, the propargyl group (-CH 2 C≡CH) is reduced to generate propargyl radicals, which can polymerize to form a thin, dense coating on the surface of the negative electrode.
[0024] In addition, the nitrogen present in the imidazolium of the compound represented by Chemical Formula 1 can act as a Lewis base, and thus Lewis acids such as HF generated from the decomposition products of the electrolyte can be easily removed, significantly preventing the problem of the transition metal being dissolved due to the attack of the positive electrode by the Lewis acid.
[0025] As a result, by using the compound represented by Chemical Formula 1 as an additive in the nonaqueous electrolyte of the present invention, it is possible to realize a lithium secondary battery that achieves improved life performance, reduced resistance, and reduced gas, particularly at high temperatures.
[0026] In one embodiment of the present invention, the compound represented by Chemical Formula 1 may be represented by the following Chemical Formula 1-1 or 1-2.
[0027] [ka]
[0028] [ka]
[0029] In the above Chemical Formula 1-1 and Chemical Formula 1-2, R1, L1, and L2 are defined as in Chemical Formula 1 above.
[0030] Specifically, when the compound represented by Chemical Formula 1 of the present invention is a compound having a zwitterion structure, which is a neutral molecule having an anion part and a cation part in the structure as in Chemical Formula 1-1, the ionic conductivity can be further improved by the zwitterion.
[0031] On the other hand, when the compound represented by Chemical Formula 1 of the present invention has the structure of Chemical Formula 1-2, the nitrogen atom of the cation moiety in the structure acts as a Lewis base, thereby effectively removing Lewis acids generated as decomposition products of the electrolyte.
[0032] In one embodiment of the present invention, L1 is -(CH 2 ) n -, where n may be an integer of 1 to 20, preferably an integer of 2 to 10, and more preferably 2 or 3. On the other hand, the L2 is -(CH 2 ) m -, where m is an integer of 1 to 10, preferably an integer of 1 to 3, and more preferably 1.
[0033] In one embodiment of the present invention, the compound represented by Chemical Formula 1 may be represented by the following Chemical Formula 1A or 1B:
[0034] [ka]
[0035] [ka]
[0036] In one embodiment of the present invention, the content of the compound represented by Chemical Formula 1 may be 0.1 wt % or more, preferably 0.3 wt % or more, more preferably 0.5 wt % or more, based on the total weight of the non-aqueous electrolyte, which is preferable in terms of showing a significant effect of removing decomposition products and improving the durability of the coating.
[0037] In addition, the content of the compound represented by Chemical Formula 1 may be 5 wt % or less, preferably 3 wt % or less, more preferably 2 wt % or less, based on the total weight of the nonaqueous electrolyte, which is preferable in that side reactions and the generation of by-products due to excess additives can be prevented. Most preferably, the content of the compound represented by Chemical Formula 1 may be 1 wt % to 2 wt % based on the total weight of the non-aqueous electrolyte solution.
[0038] (2) Additives The nonaqueous electrolyte of the present invention may further selectively contain the following additives as necessary in order to prevent electrode collapse caused by decomposition of the electrolyte in a high-voltage environment, and to further improve low-temperature high-rate discharge characteristics, high-temperature stability, prevention of overcharging, and effect of suppressing battery expansion at high temperatures.
[0039] The additive may be at least one selected from a cyclic carbonate-based compound, a halogen-substituted carbonate-based compound, a sultone-based compound, a sulfate-based compound, a phosphate-based or phosphite-based compound, a borate-based compound, a nitrile-based compound, an amine-based compound, a silane-based compound, a benzene-based compound, and a lithium salt-based compound.
[0040] The cyclic carbonate compound may be at least one selected from vinylene carbonate (VC) and vinyl ethylene carbonate (VEC), and specifically may be vinylene carbonate. The halogen-substituted carbonate compound may be fluoroethylene carbonate (FEC).
[0041] The sultone-based compound is a material capable of forming a stable SEI film on the surface of the negative electrode through a reduction reaction, and may be one or more compounds selected from 1,3-propane sultone (PS), 1,4-butane sultone, ethene sultone, 1,3-propene sultone (PRS), 1,4-butene sultone, and 1-methyl-1,3-propene sultone, and specifically may be 1,3-propane sultone (PS).
[0042] The sulfate-based compound is a material capable of forming a stable SEI film that is electrically decomposed on the surface of the negative electrode and does not crack even during high-temperature storage, and may be at least one selected from ethylene sulfate (Esa), trimethylene sulfate (TMS), and methyl trimethylene sulfate (MTMS).
[0043] The phosphate or phosphite compound may be one or more selected from lithium difluoro(bisoxalato)phosphate, lithium difluorophosphate, tris(trimethylsilyl)phosphate, tris(trimethylsilyl)phosphite, tris(2,2,2-trifluoroethyl)phosphate, and tris(trifluoroethyl)phosphite.
[0044] The borate-based compound may be lithium tetraphenylborate. The nitrile compound may be one or more selected from succinonitrile (SN), adiponitrile (ADN), acetonitrile, propionitrile, butyronitrile, valeronitrile, caprylonitrile, heptanenitrile, cyclopentanecarbonitrile, cyclohexanecarbonitrile, 2-fluorobenzonitrile, 4-fluorobenzonitrile, difluorobenzonitrile, trifluorobenzonitrile, phenylacetonitrile, 2-fluorophenylacetonitrile, 4-fluorophenylacetonitrile, ethylene glycol bis(2-cyanoethyl)ether (ASA3), 1,3,6-hexanetricarbonitrile (HTCN), 1,4-dicyano-2-butene (DCB), and 1,2,3-tris(2-cyanoethyl)propane (TCEP).
[0045] The amine compound may be at least one selected from the group consisting of triethanolamine and ethylenediamine, and the silane compound may be tetravinylsilane.
[0046] The benzene-based compound may be one or more selected from monofluorobenzene, difluorobenzene, trifluorobenzene, and tetrafluorobenzene.
[0047] The lithium salt-based compound is a compound different from the lithium salt contained in the nonaqueous electrolyte, and is lithium difluorophosphate (LiDFP; LiPO2 F 2 ), lithium bis(oxalato)borate (LiBOB; LiB(C 2 O 4 ) 2 ), lithium tetrafluoroborate (LiBF 4 ), and lithium difluoro(bisoxalato)phosphate (LiDFOP).
[0048] The non-aqueous electrolyte according to one embodiment of the present invention is vinylene carbonate (VC), vinyl ethylene carbonate (VEC), fluoroethylene carbonate (FEC), 1,3-propane sultone (PS), 1,3-propene sultone (PRS), ethylene sulfate (ESa), succinonitrile (SN), adiponitrile (ADN), ethylene glycol bis(2-cyanoethyl)ether (ASA3), 1,3,6-hexanetricarbonitrile (HTCN), 1,4-dicyano-2-butene (DCB), 1,2,3-tris(2-cyanoethyl)propane (TCEP), lithium difluorooxalate borate (LiODFB), lithium tetrafluoroborate (LiBF 4 ), lithium difluoro(bisoxalato)phosphate (LiDFOP), and lithium difluorophosphate (LiDFP).
[0049] Preferably, the non-aqueous electrolyte may further contain one or more additives selected from vinylene carbonate (VC), 1,3-propane sultone (PS), ethylene sulfate (ESa), and lithium difluorophosphate (LiDFP).
[0050] Meanwhile, the content of the additive may be 0.1 wt % to 10 wt %, preferably 0.3 wt % to 5 wt %, and more preferably 1 wt % to 3 wt %, based on the total weight of the nonaqueous electrolyte. When the content of the additive is within the above range, there is an effect of suppressing side reactions due to the formation of a coating on the positive and negative electrodes.
[0051] (3) Organic Solvent The nonaqueous electrolyte of the present invention contains an organic solvent. As the organic solvent, various organic solvents that are generally used in lithium electrolytes can be used without limitation.For example, the organic solvent can be a cyclic carbonate solvent, a linear carbonate solvent, a linear ester solvent, a cyclic ester solvent, a nitrile solvent, or a mixture thereof, and preferably includes a mixture of two or more selected from a cyclic carbonate solvent, a linear carbonate solvent, and a linear ester solvent, and more preferably includes a mixture of a cyclic carbonate solvent and a linear carbonate solvent.
[0052] The cyclic carbonate solvent is a high-viscosity organic solvent that has a high dielectric constant and can effectively dissociate the lithium salt in the electrolyte. The cyclic carbonate solvent may be one or more selected from the group consisting of ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate, and vinylene carbonate, and may preferably contain ethylene carbonate (EC) or propylene carbonate (PC).
[0053] Furthermore, the linear carbonate solvent may be one or more organic solvents having low viscosity and low dielectric constant selected from the group consisting of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate, ethyl methyl carbonate (EMC), methyl propyl carbonate, and ethyl propyl carbonate, and may preferably include ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), or diethyl carbonate (DEC).
[0054] In order to produce an electrolyte solution having high ionic conductivity, it is preferable to use a mixture of a cyclic carbonate solvent and a linear carbonate solvent as the organic solvent.
[0055] The linear ester solvent may be one or more selected from methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, and butyl propionate, and may be preferably methyl propionate, ethyl propionate, or propyl propionate.
[0056] The cyclic ester solvent may be at least one selected from γ-butyrolactone, γ-valerolactone, γ-caprolactone, σ-valerolactone, and ε-caprolactone.
[0057] The nitrile solvent may be one or more selected from succinonitrile, acetonitrile, propionitrile, butyronitrile, valeronitrile, caprylonitrile, heptanenitrile, cyclopentanecarbonitrile, cyclohexanecarbonitrile, 2-fluorobenzonitrile, 4-fluorobenzonitrile, difluorobenzonitrile, trifluorobenzonitrile, phenylacetonitrile, 2-fluorophenylacetonitrile, and 4-fluorophenylacetonitrile, and may be preferably succinonitrile.
[0058] The remaining components in the total weight of the nonaqueous electrolyte solution, excluding the organic solvent, for example, the compound represented by Formula 1, the additive, and the lithium salt, may be an organic solvent unless otherwise specified.
[0059] (4) Lithium salt The non-aqueous electrolyte of the present invention contains a lithium salt. As the lithium salt, any salt commonly used in electrolytes for lithium secondary batteries can be used without limitation. Specifically, the lithium salt has a cation of Li + The anion is F. - , Cl - , Br - , I - , NO3 - 、N(CN) 2 - 、BF 4 - 、ClO 4 - 、B 10 Cl 10 - 、AlCl 4 - 、AlO 4 - 、PF 6 - 、CF 3 SO 3 - 、CH 3 CO 2 - 、CF 3 CO 2 - 、AsF 6 - 、SbF 6 - 、CH 3 SO 3 - 、(CF 3 CF 2 SO 2 ) 2 N - 、(CF 3 SO 2 ) 2 N - 、(FSO 2 ) 2 N - 、BF 2 C 2 O 4 - 、BC 4 O 8 - 、BF 2 C 2 O 4 CHF - 、PF 4 C 2 O 4 - 、PF 2 C 4 O 8 - 、PO 2 F 2 - 、(CF 3 )2 PF 4 - , (CF 3 ) 3 PF 3 - , (CF 3 ) 4 PF 2 - , (CF 3 ) 5 PF - , (CF 3 ) 6 P - , C 4 F 9 SO 3 - , C.F. 3 CF 2 SO 3 - , C.F. 3 CF 2 (CF 3 ) 2 CO - , (CF 3 SO 2 ) 2 CH - , C.F. 3 (CF 2 ) 7 SO 3 - , and SCN - may include any one or more selected from the above.
[0060] Specifically, the lithium salt is LiPF 6 , LiClO 4 , LiBF 4 , LiN(FSO 2 ) 2 (LiFSI), LiN(SO 2 CF 3 ) 2 (LiTFSI), Lithium bis(pentafluoroethanesulfonyl)imide (LiBETI), LiSO 3 CF 3 , LiPO 2 F 2, lithium bis(oxalate)borate (LiBOB), lithium difluoro(oxalate)borate (LiFOB), lithium difluoro(bisoxalato)phosphate (LiDFOP), lithium tetrafluoro(oxalate)phosphate (LiTFOP), and lithium fluoromalonato(difluoro)borate (LiFMDFB), and preferably LiPF 6 may be also possible.
[0061] In one embodiment of the present invention, the concentration of the lithium salt in the non-aqueous organic solution containing the lithium salt and the organic solvent may be 0.5 M to 4.0 M, specifically 0.5 M to 3.0 M, more specifically 0.8 M to 2.0 M. When the concentration of the lithium salt is within the above range, it is possible to prevent the viscosity and surface tension from becoming excessively high, while sufficiently ensuring the effect of improving low-temperature output and cycle characteristics, and to obtain suitable electrolyte impregnation.
[0062] [Lithium secondary battery] Next, the lithium secondary battery according to the present invention will be described. The lithium secondary battery according to the present invention includes a positive electrode including a positive electrode active material, a negative electrode including a negative electrode active material, a separator interposed between the positive electrode and the negative electrode, and a non-aqueous electrolyte, the non-aqueous electrolyte being the non-aqueous electrolyte according to the present invention. The non-aqueous electrolyte has been described above, so a description thereof will be omitted, and other components will be described below.
[0063] (1) Positive electrode The positive electrode according to the present invention includes a positive electrode active material, and may be prepared by coating a positive electrode current collector with a positive electrode slurry including the positive electrode active material, a binder, a conductive material, a solvent, and the like, followed by drying and rolling.
[0064] The positive electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity. For example, stainless steel; aluminum; nickel; titanium; baked carbon; or aluminum or stainless steel whose surface has been treated with carbon, nickel, titanium, silver, or the like may be used.
[0065] The positive electrode active material is a compound capable of reversible intercalation and deintercalation of lithium, and is LCO (LiCoO 2 );LNO(LiNiO 2 );LMO(LiMnO 2 );LiMn 2 O 4 , LiCoPO 4 ;LFP(LiFePO 4 ); and lithium composite transition metal oxides containing nickel (Ni), cobalt (Co), and manganese (Mn). On the other hand, in the positive electrode active material, the molar ratio of nickel in the transition metals may be 60 mol % or more, preferably 70 mol % or more, and more preferably 80 mol % or more.
[0066] In one embodiment of the present invention, the lithium composite transition metal oxide may be a compound represented by the following Chemical Formula 2. That is, a positive electrode active material according to one embodiment of the present invention may contain a lithium composite transition metal oxide represented by the following Chemical Formula 2.
[0067] [Chemical formula 2] Li 1+x (Ni a Co b Mn c M d )O 2
[0068] In the formula (2), M is one or more selected from W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo; 1 + x, a, b, c, and d are respectively atomic fractions of independent elements, -0.2 ≤ x ≤ 0.2, 0.6 ≤ a < 1, 0 < b ≤ 0.3, 0 < c ≤ 0.3, 0 ≤ d ≤ 0.1, and a + b + c + d = 1.
[0069] The 1 + x represents the molar ratio of lithium in the lithium composite transition metal oxide, and -0.1 ≤ x ≤ 0.2 or 0 ≤ x ≤ 0.2 may be satisfied. When the molar ratio of lithium satisfies the above range, the crystal structure of the lithium composite transition metal oxide can be stably formed.
[0070] The a represents the molar ratio of nickel among all metals excluding lithium in the lithium composite transition metal oxide, and 0.70 ≤ a < 1, 0.80 ≤ a < 1, or 0.85 ≤ a < 1 may be satisfied. When the molar ratio of nickel satisfies the above range, it shows a high energy density and high capacity can be realized.
[0071] The b represents the molar ratio of cobalt among all metals excluding lithium in the lithium composite transition metal oxide, and 0 < b ≤ 0.20, 0 < b ≤ 0.15, or 0 < b ≤ 0.10 may be satisfied. When the molar ratio of cobalt satisfies the above range, good resistance characteristics and output characteristics can be realized.
[0072] The c represents the molar ratio of manganese among all metals excluding lithium in the lithium composite transition metal oxide, and 0 < c ≤ 0.20, 0 < c ≤ 0.15, or 0 < c ≤ 0.10 may be satisfied. When the molar ratio of manganese satisfies the above range, excellent structural stability of the positive electrode active material is shown.
[0073] In one embodiment of the present invention, the lithium composite transition metal oxide may contain one or more doping elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo. The lithium composite transition metal oxide may contain Al as the doping element. In other words, the d, which indicates the molar ratio of the doping element to all metals excluding lithium in the lithium composite transition metal oxide, is 0 <d≦0.10、0<d≦0.08、または0<d≦0.05であってもよい。 Preferably, a, b, c, and d in the formula 2 are each 0.70≦a<1, 0 <b≦0.2、0<c≦0.2、0≦d≦0.1であってもよい。
[0074] The positive electrode active material may be included in an amount of 80 wt% to 99 wt%, specifically 90 wt% to 99 wt%, based on the total weight of the solid content in the positive electrode slurry. In this case, if the content of the positive electrode active material is 80 wt% or less, the energy density may be reduced, and the capacity may be reduced.
[0075] The binder is a component that aids in binding between the active material and the conductive material and between the current collector, and may be added in an amount of 1% by weight to 30% by weight based on the total weight of the solid content in the positive electrode slurry. Examples of such binders include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber, fluororubber, or various copolymers thereof.
[0076] The conductive material is a substance that does not cause a chemical change in the battery and imparts conductivity, and may be added in an amount of 0.5% by weight to 20% by weight based on the total weight of the solid content in the positive electrode slurry.
[0077] The conductive material may be selected from conductive materials such as carbon blacks, such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; graphite powders, such as natural graphite, artificial graphite, carbon nanotubes, and graphite; conductive fibers, such as carbon fibers and metal fibers; conductive powders, such as carbon fluoride powder, aluminum powder, and nickel powder; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; and polyphenylene derivatives.
[0078] The solvent for the positive electrode slurry may contain an organic solvent such as NMP (N-methyl-2-pyrrolidone) and may be used in an amount that provides a preferred viscosity when containing the positive electrode active material, binder, conductive material, etc. For example, the positive electrode slurry containing the positive electrode active material, binder, and conductive material may be contained so that the solid content concentration is 40% by weight to 90% by weight, preferably 50% by weight to 80% by weight.
[0079] (2) Negative electrode The negative electrode according to the present invention includes a negative electrode active material, and may be manufactured by coating a negative electrode current collector with a negative electrode slurry including the negative electrode active material, a binder, a conductive material, a solvent, and the like, followed by drying and rolling.
[0080] The negative electrode current collector generally has a thickness of 3 μm to 500 μm. Such a negative electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has high conductivity, and for example, copper; stainless steel; aluminum; nickel; titanium; baked carbon; copper or stainless steel surface treated with carbon, nickel, titanium, silver, or the like; or an aluminum-cadmium alloy may be used. In addition, like the positive electrode current collector, fine irregularities may be formed on the surface to strengthen the binding force of the negative electrode active material, and it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0081] The negative electrode active material may include one or more selected from a carbon material capable of reversibly intercalating / deintercalating lithium ions; a metal or an alloy of such a metal and lithium; a metal composite oxide; a material capable of doping and dedoping lithium; lithium metal; and a transition metal oxide.
[0082] The carbonaceous material capable of reversibly intercalating / deintercalating lithium ions may be any carbonaceous negative electrode active material commonly used in lithium ion secondary batteries, and representative examples thereof include crystalline carbon, amorphous carbon, or a combination of both. Examples of the crystalline carbon include graphite such as amorphous, plate-like, flake-like, spherical, or fibrous natural graphite or artificial graphite, and examples of the amorphous carbon include soft carbon (low-temperature calcined carbon), hard carbon, mesophase pitch carbide, calcined coke, etc.
[0083] As the metal or the alloy of these metals and lithium, a metal selected from the group consisting of Cu, Ni, Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn, or an alloy of these metals and lithium may be used.
[0084] The metal composite oxides include PbO, PbO 2 , Pb 2 O 3 , Pb 3 O 4 , Sb 2 O 3 , Sb 2 O 4 , Sb 2 O 5 , GeO, GeO 2 , Bi 2 O 3 , Bi 2 O 4 , Bi 2 O 5 , Li x Fe2 O 3 (0 ≦ x ≦ 1), Li x WO 2 (0 ≦ x ≦ 1), and Sn x Me 1-x Me’ y O z (Me: Mn, Fe, Pb, Ge; Me’: Al, B, P, Si, Group 1, Group 2, Group 3 elements of the periodic table, halogen; 0 < x ≦ 1; 1 ≦ y ≦ 3; 1 ≦ z ≦ 8), one or more selected from the group consisting of may be used.
[0085] As the substance capable of doping and undoping lithium, Si, SiO x (0 < x < 2), Si-Y alloy (wherein Y is an element selected from the group consisting of an alkali metal, an alkaline earth metal, a Group 13 element, a Group 14 element, a transition metal, a rare earth element, and combinations thereof, and is not Si), Sn, SnO 2 , Sn-Y (wherein Y is an element selected from the group consisting of an alkali metal, an alkaline earth metal, a Group 13 element, a Group 14 element, a transition metal, a rare earth element, and combinations thereof, and is not Sn), etc. may be mentioned, and at least one of these and SiO 2 may be mixed and used. The element Y may be selected from the group consisting of Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db (Dubnium), Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof. Examples of the transition metal oxide include lithium-containing titanium composite oxide (LTO), vanadium oxide, lithium vanadium oxide, etc.
[0086] In one embodiment of the present invention, the negative electrode active material may be a mixture of the carbon-based material and the silicon-based material, and preferably, it may be a mixture of graphite and SiO. The negative electrode active material may be included in an amount of 80% by weight to 99% by weight based on the total weight of solids in the negative electrode slurry.
[0087] The binder is a component that helps to bond between the conductive material, the active material, and the current collector, and may be added in an amount of 1% by weight to 30% by weight based on the total weight of the solid content in the negative electrode slurry. Examples of such binders include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber, fluororubber, and various copolymers thereof.
[0088] The conductive material is a component for further improving the conductivity of the negative electrode active material, and may be added in an amount of 0.5% by weight to 20% by weight based on the total weight of the solid content in the negative electrode slurry. Such a conductive material is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and may be, for example, carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, or thermal black; graphite powder such as natural graphite, artificial graphite, carbon nanotube, or graphite with a highly developed crystal structure; conductive fiber such as carbon fiber or metal fiber; conductive powder such as carbon fluoride powder, aluminum powder, or nickel powder; conductive whisker such as zinc oxide or potassium titanate; conductive metal oxide such as titanium oxide; or conductive material such as polyphenylene derivative.
[0089] The solvent for the negative electrode slurry may include water or an organic solvent such as NMP or alcohol, and may be used in an amount that provides a preferred viscosity when the negative electrode active material, binder, conductive material, etc. are contained. For example, the negative electrode active material, binder, and conductive material may be contained so that the solid content concentration in the slurry is 30% by weight to 80% by weight, preferably 40% by weight to 70% by weight.
[0090] (3) Separator The lithium secondary battery according to the present invention includes a separator between the positive electrode and the negative electrode.
[0091] The separator separates the negative electrode and the positive electrode and provides a path for lithium ion migration. Any separator that is typically used as a separator in a lithium secondary battery can be used without any particular limitation. In particular, it is preferable that the separator has low resistance to ion migration of the electrolyte, is excellent in electrolyte impregnation ability, and is excellent in safety.
[0092] Specifically, the separator may be a porous polymer film, for example, a porous polymer film made of a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, or an ethylene / methacrylate copolymer; or a laminate structure of two or more layers thereof. Also, a normal porous nonwoven fabric, for example, a nonwoven fabric made of high-melting point glass fiber, polyethylene terephthalate fiber, or the like, may be used. Also, in order to ensure heat resistance or mechanical strength, a coated separator containing a ceramic component or a polymeric substance may be used, and may be used as a single layer or a multilayer structure.
[0093] The lithium secondary battery according to the present invention as described above can be effectively used in portable devices such as mobile phones, notebook computers, and digital cameras; and electric vehicles such as hybrid electric vehicles (HEVs).
[0094] According to another embodiment of the present invention, there is provided a battery module including the lithium secondary battery as a unit cell, and a battery pack including the same. The battery module or battery pack can be used as a power source for one or more medium- to large-sized devices, including power tools; electric vehicles, including electric vehicles (EVs), hybrid electric vehicles, and plug-in hybrid electric vehicles (PHEVs); and power storage systems.
[0095] The external shape of the lithium secondary battery of the present invention is not particularly limited, and may be a cylindrical shape using a can, a square shape, a pouch shape, a coin shape, or the like.
[0096] The lithium secondary battery according to the present invention can be used not only as a battery cell used as a power source for small devices, but also preferably as a unit battery in a medium- to large-sized battery module including a plurality of battery cells. The present invention will now be described in more detail with reference to specific examples.
[0097] <Example: Manufacture of lithium secondary battery> Example 1. (Production of non-aqueous electrolyte) Ethylene carbonate (EC): dimethyl carbonate (DMC) were mixed in a volume ratio of 30:70, and then LiPF 6 A non-aqueous organic solution was prepared by dissolving the compound represented by Chemical Formula 1A at 2 wt %, vinylene carbonate (VC) at 2 wt %, and the remaining non-aqueous organic solution were mixed to prepare a non-aqueous electrolyte solution of 100 wt %.
[0098] (Manufacture of lithium secondary batteries) N-methyl-2-pyrrolidone (NMP) was used as the positive electrode active material (Li(Ni 0.8 Co 0.1 Mn 0.1 )O 2), conductive material (carbon black), and binder (polyvinylidene fluoride) were added in a weight ratio of 97.5:1:1.5 to prepare a positive electrode slurry (solid content: 60% by weight). The positive electrode slurry was applied to a 15 μm-thick aluminum (Al) thin film as a positive electrode current collector, dried, and then roll pressed to prepare a positive electrode.
[0099] Anode active material (graphite 96wt% and SiO 4wt%), binder (SBR-CMC), and conductive material (carbon black) were added to water as a solvent in a weight ratio of 95:3.5:1.5 to prepare anode slurry (solid content: 60wt%). The anode slurry was applied to a copper (Cu) thin film as an anode current collector with a thickness of 6μm, dried, and then roll pressed to prepare anode.
[0100] The positive electrode, inorganic particles (Al 2 O 3 A polyolefin-based porous separator coated with the ZnO-based polymer and a negative electrode were sequentially stacked to prepare an electrode assembly. The assembled electrode assembly was placed in a cylindrical battery case, and the non-aqueous electrolyte prepared above was poured into the case to manufacture a lithium secondary battery.
[0101] Example 2. A lithium secondary battery was manufactured in the same manner as in Example 1, except that the content of the compound represented by Formula 1A was changed to 1 wt % when the non-aqueous electrolyte was prepared.
[0102] Example 3. A lithium secondary battery was manufactured in the same manner as in Example 1, except that the content of the compound represented by Formula 1A was changed to 1 wt % and 1,3-propane sultone (PS) was further added in the preparation of the non-aqueous electrolyte.
[0103] Example 4. A lithium secondary battery was manufactured in the same manner as in Example 1, except that the content of the compound represented by Formula 1A was changed to 0.3 wt % during the preparation of the non-aqueous electrolyte.
[0104] Example 5. A lithium secondary battery was manufactured in the same manner as in Example 1, except that the compound represented by Formula 1B was used instead of the compound represented by Formula 1A when preparing the non-aqueous electrolyte.
[0105] Example 6. A lithium secondary battery was manufactured in the same manner as in Example 5, except that the content of the compound represented by Formula 1B was changed to 1 wt % when the non-aqueous electrolyte was prepared.
[0106] Example 7. A lithium secondary battery was manufactured in the same manner as in Example 5, except that the content of the compound represented by Formula 1B was changed to 1 wt % and 1,3-propane sultone (PS) was further added in the preparation of the non-aqueous electrolyte.
[0107] Example 8. A lithium secondary battery was manufactured in the same manner as in Example 5, except that the content of the compound represented by Formula 1B was changed to 0.3 wt % during the preparation of the non-aqueous electrolyte.
[0108] Comparative Example 1 A lithium secondary battery was manufactured in the same manner as in Example 1, except that the compound represented by Formula 1A was not added during the preparation of the non-aqueous electrolyte.
[0109] Comparative Example 2 A lithium secondary battery was manufactured in the same manner as in Example 1, except that the compound represented by Formula 1A was not added and 1 wt % of 1,3-propane sultone (PS) was further added during the preparation of the non-aqueous electrolyte.
[0110] Comparative Example 3. A lithium secondary battery was manufactured in the same manner as in Example 3, except that the compound represented by the following formula C was used in place of the compound represented by formula 1A in the preparation of the non-aqueous electrolyte, and its content was changed to 0.3 wt %.
[0111] [ka]
[0112] Comparative Example 4. A lithium secondary battery was manufactured in the same manner as in Example 1, except that the compound represented by the following formula D was used in place of the compound represented by formula 1A in the preparation of the non-aqueous electrolyte, and its content was 2 wt %.
[0113] [ka]
[0114] <Experimental example: Evaluation of battery performance> Experimental Example 1. Measurement of capacity and resistance after high-temperature storage The lithium secondary batteries prepared in the Examples and Comparative Examples were subjected to an activation process, and then constant current / constant voltage (CC / CV) charging (0.05C cut off) was performed at 25° C. up to 4.25 V at a 0.5 C rate, and constant current (CC) discharging was performed at a 0.5 C rate up to 2.50 V, and the initial discharge capacity and initial resistance were measured.
[0115] The battery was then fully charged to 100% SOC under the same conditions and stored at high temperature (55°C) for 8 weeks. It was then transferred to a charger / discharger at room temperature (25°C), after which the capacity and resistance were measured again, and the capacity retention rate and resistance increase rate were calculated using the following formulas 1 and 2. The results are shown in Table 1 below.
[0116] Equation 1: Capacity retention rate (%) = (discharge capacity after high-temperature storage / initial discharge capacity) x 100 Equation 2: Resistance increase rate (%) = {(resistance after high temperature storage - initial resistance) / initial resistance} x 100
[0117] Experimental Example 2: Measurement of gas generation rate after high temperature storage After the activation process was performed on the lithium secondary batteries prepared in the examples and comparative examples, they were charged at 25° C. at a rate of 0.5C up to 4.25V under constant current / constant voltage conditions (0.05C cut off) and fully charged to 100% SOC. The fully charged batteries were stored at 72° C. for 4 weeks and then transferred to a charger / discharger at room temperature (25° C.), and the gas collected in the cylindrical can was analyzed using GC-TCD (gas chromatography-thermal conductivity detector). The relative gas generation amount of each battery was calculated based on the gas generation amount measured in Comparative Example 1 being 100%, and is shown in Table 1 below.
[0118] Experimental example 3: High temperature life evaluation After the activation process was performed on the lithium secondary batteries prepared in the Examples and Comparative Examples, they were charged at 40° C. at a 0.3 C rate up to 4.25 V with a constant current / constant voltage (CC / CV) charge (0.05 C cut off) and discharged at a 0.5 C rate up to 2.85 V with a constant current (CC) discharge.
[0119] The charge / discharge cycle was repeated 250 times, and the resistance increase rate (DCIR increase) was measured according to the following formula 3. The measurement results are shown in Table 1 below. Equation 3: Resistance increase rate (%) = {(resistance after 250 cycles - resistance after 1 cycle) / resistance after 1 cycle} x 100
[0120] Experimental Example 4: Evaluation of Thermal Safety After the lithium secondary batteries prepared in the examples and comparative examples were subjected to an activation process, they were charged at 25° C. at a rate of 0.5C up to 4.25V under constant current / constant voltage conditions (0.05C cut off) and fully charged to SOC 100%. The fully charged batteries were heated to 130° C. at a heating rate of 5° C. / min and left for 30 minutes, respectively, and a hot box evaluation experiment was performed to check for the occurrence of ignition. The results are shown in Table 1 below. If the battery did not ignite, it was marked as PASS, and if it ignited, it was marked as FAIL.
[0121] [Table 1]
[0122] From the results in Table 1, it can be seen that when the compound represented by Chemical Formula 1 is used as an electrolyte additive for a lithium secondary battery according to the present invention, not only is high-temperature durability improved and the amount of gas generation reduced, but also resistance characteristics are improved, compared to Comparative Examples 1 and 2 in which the compound represented by Chemical Formula 1 is not used, and Comparative Example 3 in which a compound represented by Chemical Formula C having a structure similar to that of Chemical Formula 1 but not containing a sulfite group is used. Meanwhile, it can be seen that in the case of Comparative Example 4, high-temperature durability is reduced because Chemical Formula D does not contain a propargyl group capable of polymerizing with vinylene carbonate (VC) to form an SEI film on the negative electrode.
[0123] In particular, it can be confirmed that the best results are obtained in all evaluation items when the content of the compound represented by Chemical Formula 1 is 1 wt% or more, and most preferably 2 wt% or more. By comparing Example 2 with Example 3 and Example 6 with Example 7, it can be confirmed that when the same content is used, further inclusion of PS shows better results, but by comparing Example 1 with Example 3 and Example 5 with Example 7, it can be confirmed that increasing the content of the compound represented by Chemical Formula 1 is more advantageous than using PS.
Claims
1. A non-aqueous electrolyte for a lithium secondary battery comprising a lithium salt, an organic solvent, and a compound represented by the following chemical formula 1: 【Chemistry 1】 In the above Chemical Formula 1, R is O - or OR1, wherein R1 is hydrogen; or an alkyl group having 1 to 10 carbon atoms; L1 is a direct bond; or an alkylene group having 1 to 30 carbon atoms; L2 is an alkylene group having 1 to 10 carbon atoms.
2. The nonaqueous electrolyte for a lithium secondary battery according to claim 1, wherein the compound represented by Chemical Formula 1 is represented by the following Chemical Formula 1-1 or 1-2: 【Chemistry 2】 【Chemistry 3】 In the above Chemical Formula 1-1 and Chemical Formula 1-2, R1, L1, and L2 are the same as defined in Chemical Formula 1 above.
3. The L1 is -(CH 2 ) n-, 2. The nonaqueous electrolyte for a lithium secondary battery according to claim 1, wherein n is an integer of 1 to 20.
4. The L2 is -(CH 2 ) m-, 2. The nonaqueous electrolyte for a lithium secondary battery according to claim 1, wherein m is an integer of 1 to 10.
5. 2. The non-aqueous electrolyte for a lithium secondary battery according to claim 1, wherein the content of the compound represented by Formula 1 is from 0.1 wt % to 5 wt % based on the total weight of the non-aqueous electrolyte.
6. 2. The non-aqueous electrolyte for a lithium secondary battery according to claim 1, wherein the content of the compound represented by Formula 1 is from 0.5 wt % to 5 wt % based on the total weight of the non-aqueous electrolyte.
7. 2. The nonaqueous electrolyte for a lithium secondary battery according to claim 1, further comprising at least one additive selected from the group consisting of vinylene carbonate, 1,3-propane sultone, ethylene sulfate, and lithium difluorophosphate.
8. 2. The nonaqueous electrolyte solution for a lithium secondary battery according to claim 1, wherein the organic solvent comprises a mixture of two or more solvents selected from the group consisting of cyclic carbonate solvents, linear carbonate solvents, and linear ester solvents.
9. a positive electrode including a positive electrode active material; a negative electrode including a negative electrode active material; a separator interposed between the positive electrode and the negative electrode; The nonaqueous electrolyte solution according to any one of claims 1 to 8, A lithium secondary battery comprising:
10. The lithium secondary battery according to claim 9 , wherein the positive electrode active material comprises a lithium composite transition metal oxide represented by the following Chemical Formula 2: [Chemical formula 2] Li 1+x (N a Co b Mn c M d )O 2 In the above Chemical Formula 2, M is at least one selected from W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo; 1+x, a, b, c, and d are the atomic fractions of each independent element, -0.2≦x≦0.2, 0.6≦a<1, 0<b≦0.3, 0<c≦0.3, 0≦d≦0.1, and a+b+c+d=1.
11. The lithium secondary battery of claim 10, wherein a, b, c, and d in the formula 2 are in the ranges of 0.70≦a<1, 0<b≦0.2, 0<c≦0.2, and 0≦d≦0.1, respectively.
Citation Information
Patent Citations
Manufacturing method of electrolyte for electrochemical element
JP2007095983A
Electrolyte additive for secondary battery, non-aqueous electrolyte for lithium secondary battery containing the same, and lithium secondary battery
JP2023524703A
Nonaqueous electrolyte for lithium secondary battery and lithium secondary battery including same
WO2013137596A1
Non-aqueous electrolyte for lithium secondary battery and lithium secondary battery comprising same
WO2020149678A1
An electrolyte for a lithium secondary battery and alithium secondary battery comprising the same
KR1020030061219A